A A Cross Sectional Study of Accident Among Prime Mover Operator at Port - Mangku, Josphine; Kenny Martinus; Zuritah A. Kadir (Progress in Engineering Application and Technology, 2024)
Accidents involving prime mover operators at port container terminals pose significant risks to both personnel and infrastructure. This cross-sectional study aims to investigate the frequency, characteristics, contributing risk factors, and preventive practices associated with accidents among prime mover operators at a well-defined port location. By encompassing the entire population, the study provides comprehensive insights into the challenges and risk factors faced by prime mover operators, including human factor, vehicle factor, road and environment factor, and weather condition factor. Data collection involves two approaches administering a structured questionnaire survey as primary data and secondary data was using journals etc. Data collected via a questionnaire distributed among 321 prime mover operators. Utilizing SPSS version 29 software, the chapter meticulously analyzes various aspects of the collected data. Surprisingly, the response rate exceeded expectations at 101%, indicating a higher engagement than anticipated. Reliability analysis revealed a strong internal consistency among measured items, denoted by a Cronbach’s Alpha value of .910. Demographic analysis highlighted that the majority of respondents were male, aged between 26 and 40, with 1 to 2 years of work experience, predominantly single, Malaysian citizens, and possessed secondary-level education. Regarding accidents, most reported no involvement, while different types and characteristics of accidents were detailed. In conclusion, this study has shown that the significant level of human factor is high (mean=4.02), vehicle factor is high (3.82), road and environment factor is medium (3.10) and weather condition factor is low(1.52). Lastly, intervention program preferences were explored, highlighting varying participation rates among different safety measures. Overall, this study provides a comprehensive and insightful examination of prime mover operators' accidents, demographics, risk factors, and intervention preferences, offering valuable insights for enhancing safety measures in this domain.